(untitled) (Transport systems and technologies, 2018)
To simulate the surfaces in the AutoCAD system with the technique of rotation, pre-create a curve that will be generated by this surface. The curve is constructed either with the use of primitives (circle, ellipse), or by analytically determined points of the curve, which can be approximated by the spline. For curves of the second order (ellipses, hy-perbola, parabola), it is possible to construct them as lines of conical sections. In this case, such a cone and a plane must be constructed, which in the intersection will create a curve with given parameters. The dependence of the parameters of the cone and the plane on the parameters of the formed parabola is proposed to be determined by methods of descriptive geometry on the basis of projective images. The study was based on the Dundelin theorem on the determination a parabola focus as a point of tangency of the inscribed sphere to the cut plane. Trigonometric ratio are obtained by the frontal projec-tion of the figures at the position that of the cut plane is perpendicular to the projection plane. An identical dependence is also derived using the profile projection of figures for the situation when the parabola is touched to the outline constituents. The introduction of a new coordinate system at in the plane of the cross-section made it possible to estab-lish the ratio of the elements of the figures according to the canonical equation of the parabola. The obtained ratio can be used at modeling process of surfaces with AutoCAD system by the technique of conical surface.